HUBUNGAN MINAT DAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN MOTIVASI MELANJUTKAN PROGRAM PROFESI NERS PADA MAHASISWA TINGKAT IV S-1 ILMU KEPERAWATAN STIKES BETHESDA - Intening, Vivi Retno; Br Sidabalok, Selly Ruth Defanna (Jurnal Kesehatan, 2018)
Background : The ratio of nurses in Indonesia is 87.65 per 100,000 population. This is still far from the 2019 target of 180 per 100,000 population. . The number of nurses in 2014 in Indonesia amountedto 237,181. Until 2014, the number of nurses with STR in Indonesia is 281,111. Objective : To know the relationship between interest and peer social support with motivation to continue Ners Profession Programof Fourt Year S-1 Nursing Students of STIKES Bethesda Yakkum Yogyakarta in 2017. Methods : This study used cross sectional research method. The technique sampling was systematic random samplingwith 104 respondents. Analysis used spearman rank. Results : Spearman rank test’s result showed the relationship between interest and motivation p-value of 0,000<0,05 with correlation coeffcient of 0,641correlated strongly and the relationship between peer social support and motivation to continue Ners Profession Program of Fourth Year S-1 Nursing Student of STIKES Bethesda Yakkum in Yogyakarta p-value0,000<0.05 with correlation coeffcient of 0,341 which means low correlation. Conclusion : There is a relationship between interest and peer social support with motivation to continue Ners Profession Programof fourth year S-1 Nursing Students of STIKES Bethesda Yakkum Yogyakarta in 2017. Suggestion : Students of STIKES Bethesda Yakkum are expected to increase their interest, peer social support, and motivation tocontinue Ners Profession Program.Keywords: Interests - Peer social support – Motivation - Fourth year.